2010
DOI: 10.1017/s135246581000010x
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of Mindfulness-Based Cognitive Therapy as a Relapse Prevention Treatment for Major Depressive Disorder

Abstract: It is suggested that ongoing MBCT skills and practice may be important for relapse prevention over the longer term. Larger randomized studies of the mechanisms of MBCT with longer follow-up periods are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 29 publications
3
48
0
1
Order By: Relevance
“…Furthermore, another compelling study found that MBCT appears to be as effective as CBT in the treatment of current depression. 214 Thus, while strong evidence for the use of MPs currently exists, additional studies are needed to further delineate the indications for their use and resolve some conflicting results. An important concern is the lack of long-term adherence data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, another compelling study found that MBCT appears to be as effective as CBT in the treatment of current depression. 214 Thus, while strong evidence for the use of MPs currently exists, additional studies are needed to further delineate the indications for their use and resolve some conflicting results. An important concern is the lack of long-term adherence data.…”
Section: Discussionmentioning
confidence: 99%
“…226 The strongest evidence is for relapse prevention in unipolar illness. 2,4,[210][211][212][213][214][215]227 Recent meta-analyses 2,227 have concluded that MBCT is effective for reducing relapses in those with three or more prior episodes. Additional conclusions from one of these studies 2 were that effectiveness for relapse prevention was similar to antidepressants at 1 year and that augmentation with MBCT could be useful for reducing residual depressive symptoms.…”
Section: Mindfulness-based Cognitive Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Sephton et al (2007) found that, in a community sample of women with fibromyalgia who completed an MBSR program, those who reported continuing to engage in formal mindfulness practice at the two-month follow-up period reported the greatest reduction in depressive symptoms. In a study of Mindfulness-Based Cognitive Therapy (MBCT), improvements in depressive symptoms over follow-up periods ranging from 12 to 34 months were significantly associated with both duration and frequency of post-treatment formal and informal mindfulness practices, although the authors did not describe their practice measures (Mathew et al 2010). The remaining studies, three with participants in MBSR programs (Davidson et al 2004; Kabat-Zinn et al 1987; 1992) and one following a 10-day intensive mindfulness meditation retreat (Ostafin et al 2006), did not find significant relationships between amount of post-intervention practice and longer-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…MBCT appears to be equivalent to maintenance medication for relapse prevention [ 13 -15 ]. Gains from MBCT treatment were maintained over a 34-month follow-up period in one study [ 16 ] and 5-year follow-up period in another [ 17 ].…”
Section: Use Of Mbct For Prevention Of Depressive Relapsementioning
confidence: 96%